Extracellular bone morphogenetic protein modulator BMPER and twisted gastrulation homolog 1 preserve arterial‐venous specification in zebrafish blood vessel development and regulate Notch signaling in endothelial cells. (9th March 2018) - Esser, Jennifer Susanne; Steiner, Rahel Elisabeth; Deckler, Meike; Schmitt, Hannah; Engert, Bianca; Link, Sandra; Charlet, Anne; Patterson, Cam; Bode, Christoph; Zhou, Qian; Moser, Martin
Abstract : The bone morphogenetic protein (BMP) signaling pathway plays a central role during vasculature development. Mutations or dysregulation of the BMP pathway members have been linked to arteriovenous malformations. In the present study, we investigated the effect of the BMP modulators bone morphogenetic protein endothelial precursor‐derived regulator (BMPER) and twisted gastrulation protein homolog 1 (TWSG1) on arteriovenous specification during zebrafish development and analyzed downstream Notch signaling pathway in human endothelial cells. Silencing of bmper and twsg1b in zebrafish embryos by morpholinos resulted in a pronounced enhancement of venous ephrinB4a marker expression and concomitant dysregulated arterial ephrinb2a marker expression detected by in situ hybridization. As arteriovenous specification was disturbed, we assessed the impact of BMPER and TWSG1 protein stimulation on the Notch signaling pathway on endothelial cells from different origin. Quantitative real‐time PCR (qRT‐PCR) and western blot analysis showed increased expression of Notch target gene hairy and enhancer of split, HEY1/2 and EPHRINB2. Consistently, silencing of BMPER in endothelial cells by siRNAs decreased Notch signaling and downstream effectors. BMP receptor antagonist DMH1 abolished BMPER and BMP4 induced Notch signaling pathway activation. In conclusion, we found that in endothelial cells, BMPER and TWSG1 are necessary for regular Notch signaling activity and in zebrafish embryos BMPER and TWSG1 preserve arteriovenous specification to prevent malformations. Abstract : The bone morphogenetic protein (BMP) signaling pathway plays a central role during vasculature development. Silencing of bmper and twsg1b in zebrafish embryos by morpholinos resulted in increased venous ephrinB4a and concomitant dysregulated arterial ephrinb2a marker expression, which was confirmed in human endothelial cells. Silencing of bone morphogenetic protein endothelial precursor‐derived regulator or application of BMP inhibitor dorsomorphin homolog 1 prevented Notch pathway activation and increased ephrin receptor b4a expression.